COMPRESSIVE STRENGTH AND DURABILITY PERFORMANCE OF MORTAR CONTAINING PALM OIL BOILER CLINKER AGGREGATE, RICE HUSK ASH, AND CALCIUM BENTONITE - Kueaket, Kamolchanok; Tonnayopas, Danupon (Journal of Applied Engineering Science, 2020)
The utilization of local waste by-products as a building material has attracted great attention for an environmental sustainability and become a fundamental part of sustainable construction. In this experimental research, the local palm oil industrial waste and agricultural waste are utilized for the green mortar production. To examine the compressive strength and the durability performance of the green mortar mixtures, Palm oil boiler clinker (POBC) was used as a substitution material for natural fine aggregate. An ordinary Portland cement was partially replaced by rice husk ash (RHA) and calcium bentonite (CB) in the proportion of 10%, 20%, and 30% by weight of cement. The compressive strength, water absorption, porosity, durability against sulphuric acid and sodium sulphate solutions, and microstructures of the POBC mortar mixtures were evaluated at the curing age of 7, 28, and 56 days. The experimental results revealed that the compressive strength, the water absorption, the porosity, and the durability characteristic of POBC mortar incorporating rice husk ash and calcium bentonite were improved by long-term curing. Furthermore, the 56-day’s POBC mortar incorporating up to 30% of rice husk ash and 10% of calcium bentonite yielded the superior resistance to sulphuric acid and sodium sulphate attacks.
Keywords: Palm oil boiler clinker; rice husk ash; calcium bentonite; compressive strength; sulphuric acid and sodium sulphate resistance